Characteristic of Sq current based on seasonal variation in different phases of solar cycle / Mohd Anuar N. ...[et al.] - N., Mohd Anuar; M. H., Jusoh; N., Abdul Hadi; S. A., Enche Ab Rahim (UiTM Press, 2018)
The ionospheric current (Sq) variation is changeable throughout a year. This study is aimed to examine the behavior of Sq variation in different phases of the solar cycle. The horizontal component has been used to measure the monthly diurnal variation, Sq (H) and MSq (H) based on seasonal variation. The magnetic data were extracted from magnetic data acquisition system (MAGDAS) situated at Langkawi station (Geog. Lon. 99.68◦E, Geog. Lat. 6.30◦N), Malaysia. The data were collected in 2008 and 2012 to represent a different phase of the solar cycle. The result of the numerical simulation indicates that the maximum amplitude of Sq (H) values were 72.96 nT and 115.16 nT in October 2008 and September 2012, respectively. Moreover, the Sq (H) variation was generally low during night time and oscillated between -21.54 nT and 5 nT for both years. The Sq (H) amplitude was high at low latitude, specific to equatorial region due to the superimposition of Sq and EEJ current. Furthermore, the active CEJ occurred within 06:00 LT to 18:00 LT. The higher magnitude of CEJ were -27.96 nT and -35.51 nT were observed in 2008 and 2012, respectively. Both maximum readings occurred in May around 06:00 LT – 07:00 LT was due to the consequence of late interchange process between nighttime westward current to daytime eastward current flow. The seasonal mean variation revealed the maximum of MSq (H) was 66.72 nT and 96.51 nT in 2008 and 2012, respectively. Both maxima values were peaked during Equinox season resulting from the strong dynamo process and great solar thermal heating with minimal loss rates other than, during Equinox, the Sun exists right above the equator line.